ANALISIS PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN OBYEK AGROWISATA (STUDI KASUS DI KUSUMA AGROWISATA KOTA BATU, MALANG) - Novi Itsna Hidayati; Maulidlotul Dwi Kurniawati Dwi Kurniawati (Agriculture Faculty of Flores University, 2018)
Agrotourism is defined as a form of tourism activity that utilizes agribusiness as a tourism object with the aim of expanding knowledge, experience, recreation, and business relationship in agriculture. One of the agro tourism destinations in East Java is Kusuma Agrowisata with a unique commodity that is cultivated is a typical commodity of Malang City that is Malang Apples. Kusuma Agrowisata has tried to offer tour packages, but the tour package does not contain elements that are in accordance with the wishes of visitors. The purpose of this study is to identify the characteristics of visitors related to the consumer decision-making process in choosing the object Kusuma Agrowisata and analyze the factors that influence consumer decisions in Kusuma Agro tourism object. The data used are primary data and secondary data. Primary data derived from interviews with visitors agro-tourism and answers questionnaires from respondents. The secondary data comes from several libraries relevant to the research topic. Sampling was done by using convenience sampling method as many as 100 people. The analytical tool used is descriptive analysis and multiple linear regression analysis using SPSS 15.0 softwere help.By using multiple linear regression method, it can be concluded that the most influential variable on consumer decision variables is the price variable with regression coefficient value of 0.375, while the distance variables have positive but not significant influence with regression coefficient value of 0.148, and income variable has no positive effect and also not significant with regression value of -0, 385.